Inhibition of osteolysis and increase of bone formation after local administration of siRNA-targeting RANK in a polyethylene particle-induced osteolysis model. (February 2015) - Córdova, L.A.; Trichet, V.; Escriou, V.; Rosset, P.; Amiaud, J.; Battaglia, S.; Charrier, C.; Berreur, M.; Brion, R.; Gouin, F.; Layrolle, P.; Passuti, N.; et al.
Graphical abstract: Abstract: Receptor activator of nuclear factor kappa-B (RANK) and RANK-ligand are relevant targets for the treatment of polyethylene particle-induced osteolysis. This study assessed the local administration of siRNA, targeting both human RANK and mouse Rank transcripts in a mouse model. Four groups of mice were implanted with polyethylene (PE) particles in the calvaria and treated locally with 2.5, 5 and 10 μg of RANK siRNA or a control siRNA delivered by the cationic liposome DMAPAP/DOPE. The tissues were harvested at day 9 after surgery and evaluated by micro-computed tomography, tartrate-resistant acid phosphatase (TRAP) immunohistochemistry for macrophages and osteoblasts, and gene relative expression of inflammatory and osteolytic markers. 10 μg of RANK siRNA exerted a protective effect against PE particle-induced osteolysis, decreasing the bone loss and the osteoclastogenesis, demonstrated by the significant increase in the bone volume ( P < 0.001) and by the reduction in both the number of TRAP + cells and osteoclast activity ( P < 0.01). A bone anabolic effect demonstrated by the formation of new trabecular bone was confirmed by the increased immunopositive staining for osteoblast-specific proteins. In addition, 5 and 10 μg of RANK siRNA downregulated the expression of pro-inflammatory cytokines ( P < 0.01) without depletion of macrophages . Our findings show that RANK siRNA delivered locally by a synthetic vector may be an effective approach for reducing osteolysis and may even stimulate bone formation in aseptic loosening of prosthetic implants.